Nanoporous Hydrogen Bonded Polymeric Microparticles: Facile and Economic Production of Cross Presentation Promoting Vaccine Carriers. (30th April 2014) - Dierendonck, Marijke; Fierens, Kaat; De Rycke, Riet; Lybaert, Lien; Maji, Samarendra; Zhang, Zhiyue; Zhang, Qilu; Hoogenboom, Richard; Lambrecht, Bart N.; Grooten, Johan; Remon, Jean Paul; De Koker, Stefaan; et al.
<x xml:space="preserve">Abstract</x> Nanoporous microparticles are produced in a single step based on hydrogen bonding between a neutral polymer and tannic acid. These particles are stable in physiological medium, are non‐toxic to in vitro cultured cells, and can efficiently encapsulate proteins. In vitro and in vivo experiments show that these porous hydrogen bonded microparticles are able to induce antigen‐specific cellular and humoral immune responses against encapsulated vaccine antigens. Considering the easy and low cost manufacturing of this dry powder formulation from approved readily available components, it is anticipated that this technology holds great promise for the formulation of vaccines for developing countries or for pandemic vaccines where long term storage under refrigerated conditions is a major issue. Additionally, due to the versatility of the approach facilitates straightforward co‐encapsulation of a wide variety of additional components to further modulate the immune response.